Knowledge Mapping on Maize (Zea mays L) Production Technologies by The Farmers of Karimnagar District in Telangana State - N. Venkateshwar Rao, P.K. Jain , M. Jagan Mohan Reddy and N. Kishor Kumar, (Indian Journal of Extension Education, 2017)
The present paper highlights the knowledge levels of farmers on maize production technologies in Karimnagardistrict of Telangana State. Ex-post facto research design was adopted for study. Total ninety (90) farmers wereselected for study of maize crop knowledge mapping. High level of knowledge of maize production technologieswas observed among the KVK Jammikunta adopted farmers compared to the non-adopted farmers.